2018
DOI: 10.1098/rspb.2018.0849
|View full text |Cite
|
Sign up to set email alerts
|

Timing of perineuronal net development in the zebra finch song control system correlates with developmental song learning

Abstract: The appearance of perineuronal nets (PNNs) represents one of the mechanisms that contribute to the closing of sensitive periods for neural plasticity. This relationship has mostly been studied in the ocular dominance model in rodents. Previous studies also indicated that PNN might control neural plasticity in the song control system of songbirds. To further elucidate this relationship, we quantified PNN expression and their localization around parvalbumin interneurons at key time-points during ontogeny in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 51 publications
4
36
0
Order By: Relevance
“…As aromatase is similarly expressed in NCM across development, changes in precursor androgens may explain previously observed age-dependent differences in baseline E2 in NCM across the critical period (Chao, et al, 2014), specifically in parallel with the maturation of the testes. Further, our findings with parvalbumin are in-line with recent findings that find that PV cell density is largely unchanged in across development in the NCM of in male and female zebra finches, as well as other auditory forebrain nuclei (Cornez et al, 2018). Therefore, PV-dependent inhibitory tone and estrogen production remain relatively unchanged across development, suggesting important roles throughout the juvenile period in males.…”
Section: Developmental and Regional Shifts In Neuronal Cell Density Isupporting
confidence: 91%
“…As aromatase is similarly expressed in NCM across development, changes in precursor androgens may explain previously observed age-dependent differences in baseline E2 in NCM across the critical period (Chao, et al, 2014), specifically in parallel with the maturation of the testes. Further, our findings with parvalbumin are in-line with recent findings that find that PV cell density is largely unchanged in across development in the NCM of in male and female zebra finches, as well as other auditory forebrain nuclei (Cornez et al, 2018). Therefore, PV-dependent inhibitory tone and estrogen production remain relatively unchanged across development, suggesting important roles throughout the juvenile period in males.…”
Section: Developmental and Regional Shifts In Neuronal Cell Density Isupporting
confidence: 91%
“…Half a series (two non-adjacent wells; 240 mm between sections) were double-labeled in a single assay for PV and chondroitin sulfate, one of the main components of the PNNs, following a previously described protocol (Balmer et al, 2009;Cornez et al, 2015Cornez et al, , 2017bCornez et al, , 2018. Briefly, sections were blocked in 5% normal goat serum (NGS) diluted in Tris-buffered saline (TBS) with 0.1% Triton X-100 (TBST) for 30 min.…”
Section: Tissue Collection and Immunohistochemistrymentioning
confidence: 99%
“…Developmental song learning occurs during a sensitive period of neural plasticity associated with neurogenesis (Nordeen and Nordeen, 1988;Kirn and DeVoogd, 1989;Bottjer and Arnold, 1997) and synaptic pruning (Miller-Sims and Bottjer, 2012) in the song control system. Additionally it was recently suggested that perineuronal nets (PNNs) could play an important role in the regulation of sensitive periods for vocal learning in a closed-ended learner species, the zebra finch, Taeniopygia guttata (Balmer et al, 2009;Cornez et al, 2017bCornez et al, , 2018. PNN are aggregations of chondroitin sulfate proteoglycans, tenascin R, hyaluronic acid and binding proteins that form a scaffold mainly around fast spiking interneurons expressing parvalbumin (PV; Deepa et al, 2006;Wang and Fawcett, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PNN expression peaks in adulthood but is minimal in newborn and aged animals (Yamada & Jinno, ). The appearance of PNNs in juveniles coincides with the closing of critical developmental periods (Cornez et al, ; Pizzorusso et al, ), helping to solidify active synaptic networks (Dityatev et al, ). Loss of PNNs in the brain has been linked to brain diseases associated with neurological and cognitive dysfunction, including epilepsy (McRae & Porter, ), schizophrenia (Shah & Lodge, ), and Alzheimer's disease (Morawski, Brückner, Jäger, Seeger, & Arendt, ).…”
Section: Introductionmentioning
confidence: 99%